ANALISIS KORELASI TINGKAT PENGETAHUAN DISIPLIN KEDOKTERAN DAN PELAKSANAAN PRAKTIK KEDOKTERAN YANG BAIK PADA DOKTER GIGI PRAKTIK SWASTA - , Hananto Anggoro Wiryawan, drg. Soetomo Nawawi, DPH.Dent., Sp.Perio (K) ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The guideline for the implementation of good medical practice is a guide from Indonesian Medical Council (KKI) for doctors and dentists in clinical practice. This study aims to determine and assess the relationship between the knowledge level of medical disciplinary, experience factor, and educational level in the implementation of good medical practice by private dentists in Sleman. The study design was cross sectional quantitative approach. This research was followed by 103 dentists who practice in Sleman region. The knowledge level of medical disciplinary, the implementation of good medical practice, the experience factors and educational level was assessed and obtained through a questionnaire. Logistic regression analysis was used on analysis data, with 95% confidence level. There were no significant associations between the knowledge level of medical disciplinary (p = 0.99) and the education level (p = 0.84) on the implementation of good medical practice. There is a significant association between the experience factors (p = 0.00) on the implementation of good medical practice. More experience doctor, the better implementation of medical practice.